2012
DOI: 10.1007/s00441-012-1324-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of anoctamin 1 and anoctamin 2 chloride channels in the mammalian nose

Abstract: Calcium-activated chloride channels are expressed in chemosensory neurons of the nose and contribute to secretory processes and sensory signal transduction. These channels are thought to be members of the family of anoctamins (alternative name: TMEM16 proteins), which are opened by micromolar concentrations of intracellular Ca(2+). Two family members,ANO 1 (TMEM16A) and ANO 2 (TMEM16B), are expressed in the various sensory and respiratory tissues of the nose.We have examined the tissue specificity and sub-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 91 publications
2
60
2
Order By: Relevance
“…Its molecular correlate has recently been identified as TMEM16A/anoctamin1 (Amjad et al 2015), the founding member of the anoctamin family of Ca 2+ -activated Cl − channels (Caputo et al 2008;Schroeder et al 2008;Yang et al 2008). While different groups have demonstrated expression of both anoctamin1 and anoctamin2 in VSNs (Rasche et al 2010;Billig et al 2011;Dauner et al 2012;Dibattista et al 2012), vomeronasal Ca 2+ -activated Cl − currents were abolished in conditional anoctamin1 null mice (Amjad et al 2015). For interpretation of these results, however, it is essential to determine whether vomeronasal Cl − channels contribute a strongly depolarizing current or, by contrast, if anoctamin1 activation mediates membrane hyperpolarization or shunting inhibition.…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…Its molecular correlate has recently been identified as TMEM16A/anoctamin1 (Amjad et al 2015), the founding member of the anoctamin family of Ca 2+ -activated Cl − channels (Caputo et al 2008;Schroeder et al 2008;Yang et al 2008). While different groups have demonstrated expression of both anoctamin1 and anoctamin2 in VSNs (Rasche et al 2010;Billig et al 2011;Dauner et al 2012;Dibattista et al 2012), vomeronasal Ca 2+ -activated Cl − currents were abolished in conditional anoctamin1 null mice (Amjad et al 2015). For interpretation of these results, however, it is essential to determine whether vomeronasal Cl − channels contribute a strongly depolarizing current or, by contrast, if anoctamin1 activation mediates membrane hyperpolarization or shunting inhibition.…”
Section: +mentioning
confidence: 99%
“…While the absence of anoctamin1 expression in the VNO microvillar layer after conditional knockout of Ano1 in OMP-positive mature sensory neurons indicates VSNspecific expression of this isoform (Amjad et al 2015), other family members-for example, anoctamin2 (Rasche et al 2010;Billig et al 2011;Dauner et al 2012)-could carry Ca 2+ -activated Cl − currents in vomeronasal sustentacular cells. Therefore, members of the same ion channel family could exert opposite functions in the 2 main cell types of the VNO sensory epithelium.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…The standard extracellular solution contained (mM) 140 NaCl, 5 KCl, 2 CaCl 2 , 1 MgCl 2 , 10 glucose, and 10 HEPES, pH 7.4. The standard intracellular solution contained (mM) 140 CsCl, 10 HEPES, 10 HEDTA (or 5 EGTA), pH 7.2, and no added Ca 2+ for the nominally 0 Ca 2+ solution, or various amounts of CaCl 2 , as calculated with the program WinMAXC (C. Patton, Stanford University, Stanford, CA), to photoreceptors (Stöhr et al, 2009;Billig et al, 2011;Dauner et al, 2013), in hippocampal cells (Huang et al, 2012b), in the cilia of olfactory sensory neurons, and in the microvilli of vomeronasal sensory neurons (Stephan et al, 2009;Hengl et al, 2010;Rasche et al, 2010;Sagheddu et al, 2010;Billig et al, 2011;Dauner et al, 2012;Dibattista et al, 2012;Maurya and Menini, 2013). Studies with knockout mice for TMEM16A or TMEM16B (Rock and Harfe, 2008;Billig et al, 2011) or knockdown of these channels further confirmed a reduction in CaCC activity (Flores et al, 2009;Galietta, 2009;Hartzell et al, 2009;Huang et al, 2012a;Kunzelmann et al, 2012a,b;Pifferi et al, 2012;Sanders et al, 2012;Scudieri et al, 2012).…”
Section: Ionic Solutionsmentioning
confidence: 99%
“…TMEM16A is expressed in secretory cells, smooth muscle cells, and several other cell types (Huang et al, 2009(Huang et al, , 2012a, including supporting cells in the olfactory and vomeronasal epithelium (Billig et al, 2011;Dauner et al, 2012;Dibattista et al, 2012;Maurya and Menini, 2013) and microvilli of vomeronasal sensory neurons (Dibattista et al, 2012). TMEM16B is expressed at the synaptic terminal of…”
Section: Introductionmentioning
confidence: 99%